Pulmonary histoplasmosis on the Chinese mainland: two case reports and literature review - Chen, Qi; Guo, Wei; Guo, Wenjia; Mu, Xiangdong; Guo, Jun (The Journal of Infection in Developing Countries, 2024)
Introduction: Pulmonary histoplasmosis is a fungal disease that is endemic in North and Central America. It is relatively rare in China and commonly misdiagnosed as tuberculosis or cancer due to nonspecific clinical and radiographic manifestations. Rapid and accurate pathogen tests are critical for the diagnosis of pulmonary histoplasmosis. Methodology: We report two cases of pulmonary histoplasmosis. We collected all the relevant case reports on the Chinese mainland (from 1990 to 2022) to analyze features of this disease among Chinese patients. Results: A total of 42 articles reporting 101 cases were identified, and the two cases reported in this article were also included for analysis. Sixty-three (61.2%) patients had respiratory symptoms and 35 (34.0%) patients were asymptomatic. The most common radiographic findings were pulmonary nodules or masses (81.6%). Twenty-two (21.4%) patients were misdiagnosed as tuberculosis, and 37 (35.9%) were misdiagnosed as lung tumors before pathological findings. Metagenomic next‑generation sequencing (mNGS) testing provided a rapid diagnostic and therapeutic basis for three patients. Conclusions: Clinical features and imaging findings of pulmonary histoplasmosis are not specific. Relevant epidemiological history and timely pathogen detection are important for diagnosis. mNGS can shorten the time required for diagnosis and allow earlier initiation of targeted antibiotic therapy.